XIX. Analysis of Enterprise Digital Transformation Under the Background of “One Belt and One Road” - a Case Study of Dashang Tiangou - Yue, Haiyi; Li, Min (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
With the rapid development of digital trade, many real enterprises have gradually joined the wave of transformation and upgrading. Taking Dashang Group as an example, this study deeply discusses the impact of trade digitalisation on enterprise transformation and upgrading. The study finds that digital transformation helps improve enterprises' market competitiveness but also needs to cope with challenges such as technology updates and data security. Finally, this paper puts forward policy recommendations and points out research limitations and future research directions. This study not only helps to understand the impact of trade digitalisation on enterprise transformation and upgrading but also provides a valuable reference for real enterprises to achieve sustainable development in the fierce market competition.